PENGEMBANGAN MEDIA PEMBELAJARAN BAHASA INDONESIA BERBASIS PAPAN KOSAKATA PADA KEMAMPUAN MEMBACA SISWA KELAS II SD N 04 KOTO BARU - Aprimadedi; Amar Salahuddin; Septa Tuti Ariyani (STKIP Subang, 2024)
This research is motivated by the limited learning media and teachers in the process of teaching reading have not used media that is interesting for students at SDN 10 Koto Baru. Learning that uses media is really needed to support learning activities so that learning objectives are achieved. The aim of this research is to produce panca media (reading boards) to improve reading skills in class II Indonesian language learning at SDN 04 Koto Baru that are valid, practical and effective. The research method used in this research in the Research and Development (R&D) method. The model used is the ADDIE model which consists of 5 stages. Namely analysis, design, development, implementation, evaluation. The results of the five media (reading board) validation were assessed by six expert validators, namely getting an average score in the valid category. The results of the validation of the teaching module were assessed by three expert validators, namely getting an average score of 92,40% in the valid category. The results of the teacher response questionnaire data analysis, which was assessed by one teacher, obtained an average of 75% in the very practical category. Based on the results of the trial, student responses reached 95% in the very practical category. The results of the learning effectiveness assessment for class II students obtained an average of 82,35% in the very effective category.